Topical Treatment and Aesthetic Procedures in Management of Acne Vulgaris - Nowińska, Bianka; Brzozowska, Patrycja; Bińczyk, Wiktoria; Lissak, Karina; Siudek, Bartosz; Dróżdż, Olrgierd (Quality in Sport, 2024)
Acne vulgaris is a common, chronic inflammatory skin disease affecting up to 80% of young adults and adolescents. The pathogenesis of acne is multifactorial and involves the pilosebaceous units of the skin. As a result of the disease process, skin lesions such as open and closed comedones, nodules, pustules, and papules appear on the skin. In recent years, acne has been increasingly observed in younger patients, which is associated with the earlier onset of puberty. Moreover, acne is increasingly diagnosed in individuals over 20 years of age, particularly in women, which is referred to as adult female acne (AFA). Effective and rapid implementation of treatment is crucial to prevent complications such as post-inflammatory hyperpigmentation and acne scars, as well as to mitigate the negative psychological impact of the disease on patients. The article discusses both topical treatment and aesthetic medicine procedures in the management of acne vulgaris. Topical treatments include the use of retinoids, antibiotics, benzoyl peroxide, clascoterone, dapsone, azelaic acid, and combination therapies. Aesthetic procedures such as chemical peels, microdermabrasion, photodynamic therapy, blue light therapy, and laser therapies can be beneficial as adjunctive treatments. The article also addresses the issue of acne as a comorbid condition in patients seeking aesthetic medicine treatments, even if it is not the primary reason for their visit.